Characteristics Of Binary Blended Mortar And Concrete With Coal Bottom Ash Aggregate And Precipitated Calcium Carbonate Additive - Khaw Le Ping, Kevin (2023)
The goal of this study is to refine the grading of CBA to obtain the most optimum grading of CBA that can be use as fine aggregate replacement material in a binary blended mix containing OPC and GGBS. Furthermore, additional study on the influence of precipitated calcium carbonate (PCC) as an additive in binary blended mortar/concrete containing graded CBA as a fine aggregate replacement will be investigated.